2010
DOI: 10.3354/meps08449
|View full text |Cite
|
Sign up to set email alerts
|

Relative predation risk for fishes along a subtropical mangrove–seagrass ecotone

Abstract: Many fishes shelter in mangrove habitats by day and forage mostly in seagrass beds by night. This pattern of diel habitat use has been attributed to a predator avoidance strategy, whereby predation risk is reduced by alternating between the cover afforded by prop-roots during the day and darkness at night. We employed a series of diel tethering experiments in Biscayne Bay (Florida, USA) to empirically examine whether relative predation pressure on fishes is lower at night than during the day and to compare rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 44 publications
1
21
0
Order By: Relevance
“…In back reef systems, seascape attributes have been shown to be a primary determinant of habitat use of fishes (Pittman et al 2007). Many coastal fishes, including snapper, generally prefer mangroves surrounded by dense seagrass (Pittman et al 2007) since mangrove prop roots provide shelter (Hammerschlag et al 2010) and seagrass beds contain high densities of prey items for coastal fishes (Orth et al 1984). In the present study system, potential resource pools, such as seagrass, were patchily distributed across the creek system.…”
Section: Discussionmentioning
confidence: 79%
“…In back reef systems, seascape attributes have been shown to be a primary determinant of habitat use of fishes (Pittman et al 2007). Many coastal fishes, including snapper, generally prefer mangroves surrounded by dense seagrass (Pittman et al 2007) since mangrove prop roots provide shelter (Hammerschlag et al 2010) and seagrass beds contain high densities of prey items for coastal fishes (Orth et al 1984). In the present study system, potential resource pools, such as seagrass, were patchily distributed across the creek system.…”
Section: Discussionmentioning
confidence: 79%
“…To seasonally correspond with the period of seine sampling from July to September 2008 (wet season), we assessed nocturnal patterns of predator encounter rates along our transects using tethering experiments (Hammerschlag et al 2010a). Pinfish Lagodon rhomboides were used as bait because individuals in the size range corresponding with the focal fishes were readily available from commercial suppliers and pilot studies demonstrated that pinfish were both physically and behaviorally robust to our tethering process (Hammerschlag et al 2010a). Specifically, during pilot work, no fish died, exhibited signs of injury, or broke from their tether lines.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, to secure the tether to the center line, it was connected to the center line using a snap-swivel (0.5 g). This snap-swivel attachment permitted pinfish to move freely in a vertical cylinder, with a 2 m diameter, from the seagrass to the water surface (Hammerschlag et al 2010a).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations